Evaluation of E-Learning Governance Using COBIT 2019 DSS at Universitas Indonesia Mandiri - Sella Andira Bintang Wulandari; Agus Komarudin; Ribut Julianto; Muawan Bisri (Jurnal JEETech, 2026)
This study aims to evaluate the governance of e-learning services using the COBIT 2019 framework, specifically within the Deliver, Service, and Support (DSS) domain. The research adopts a quantitative evaluative approach with a cross-sectional design, where data were collected from 30 respondents consisting of IT staff, lecturers, and students using a structured questionnaire. Data analysis was conducted through validity and reliability testing, capability level measurement, and gap analysis. The results show that all questionnaire items are valid and reliable, indicating that the instrument is suitable for measuring e-learning governance. The capability level analysis reveals an average score of 3.34, corresponding to Level 3 (Established Process). This indicates that governance processes have been implemented in a structured and consistent manner, although they have not yet reached the optimal level. The gap analysis shows that most DSS subdomains have a gap value of 2 compared to the target Level 5 (Optimizing Process), indicating the need for further improvement. The largest gaps are identified in incident management, problem management, service continuity, and business process control, suggesting that governance practices are still predominantly reactive. Therefore, organizations are encouraged to strengthen proactive governance through continuous improvement, integrated monitoring, and data-driven decision-making. This study provides practical insights for improving e-learning service governance and supports decision-making in higher education institutions. However, the findings are based on respondents’ perceptions and a cross-sectional design, which may not fully capture dynamic changes over time.